Costing techniques in supply chain cost management: A systematic literature review - Bilkis Akhter; Md. Maksudur Rahman Sarker (Journal of Accounting, Business and Management (JABM), 2026)
This article aims to present an integrated synthesis of the key components of supply chain cost management (SCCM) practices. To achieve this objective, we conducted a rigorous systematic literature review of scholarly publications focusing on SCCM. A structured content analysis was performed on carefully selected studies published over the past two decades in English-language, peer-reviewed journals. The findings indicate that both internal and inter-organizational costing techniques play a significant role in shaping effective SCCM practices and are positively associated with improved SCCM outcomes. By synthesizing the existing literature, this study identifies internal and inter-organizational costing techniques as fundamental components of SCCM and clarifies their relationships with various cost management outcomes within supply chains. These techniques emphasize coordinated and harmonized practices among supply chain partners to achieve greater cost efficiency and transparency. The study also highlights several avenues for future research in this domain. Furthermore, it provides practical managerial implications for supply chain partners seeking to strengthen cost management performance across their supply networks.